Shattered Dream in Gopinath Mohanty’s Paraja - Yadav, Prabhu Ray (Pursuits: A Journal of English Studies, 2023)
This paper attempts to analyze an amazing picture of the tribal people as known Paraja in the third world countries. They live around the river and ponds of the dense forest. Through the acts of tyranny and atrocity, the moneylenders, exploit their illiteracy and human rights. The unity of Paraja illustrates poverty-ridden Sukru Jani, the protagonist of the novel, Paraja. It portrays the sense of loss and feeling of revenge grown in the tribal people at the end. Though poor and illiterate, he is a giant pillar against the social power system. The novel shows how the moneylender or governor harasses and compels the tribal community. The tribal people innocently fall in the coil of the village landlord agency of the government, because they are not skilled and knowledgeable. They are culturally deprived and exploited by the moneylender in the society.